Development and validation of an UHPLC-qTOF-MS method for the quantification of cyclic polyesters oligomers in pasta by applying a modified QuEChERS clean-up. (15th June 2021) - Tsochatzis, Emmanouil D.; Alberto Lopes, Joao; Gika, Helen; Kastrup Dalsgaard, Trine; Theodoridis, Georgios
Highlights: Fast UHPLC-qTOF-MS analytical method. Analysis of selected polyester cyclic oligomers. Oligomers resulting from polyester food contact materials (FCM) Method development and validation. QueChERS clean-up with alumina (Al2 O3 ) and primary secondary amine (PSA). Applicability of the method to real food (pasta). Abstract: An Ultra High-Performance Liquid chromatography method quadruple time-of-flight mass spectrometry has been developed for the analysis of 11 cyclic polyesters oligomers, following a modified QuEChERS clean-up with alumina/primary secondary amine, in pasta. Target analytes were polyethylene terephthalate (PET) 1 st series cyclic dimer to heptamer, polybutylene terephthalate (PBT) dimer to pentamer and a polyurethane oligomer. Standard addition method was applied for the calibration, and the limits of quantification ranged from 3.2 to 17.2 ng g −1 . Recoveries ranged from 86.4 to 109.8%, RSDs were lower than 12% for all analytes, and matrix effect never exceeded ± 2.5%. The method was successfully applied to real commercial pasta samples, where the PET 1 st series cyclic trimer was the most abundant oligomer, being found in all tested samples. The 1 st series PET cyclic dimer and tetramer, as well as 1, 4, 7-trioxacyclotridecane-8, 13-dione, were found in considerable amounts. Traces of the 2 nd and 3 rd series PET cyclic dimers were also found.